93 Genomic basis of antibody response to porcine reproductive and respiratory syndrome virus vaccination. (30th November 2020) - Sanglard, Letícia P; Fernando, Rohan L; Gray, Kent; Linhares, Daniel C L; Dekkers, Jack; Niederwerder, Megan C; Serão, Nick
Abstract: Antibody (Ab) response to natural infection with porcine reproductive and respiratory syndrome (PRRS) virus has been shown to be highly heritable (~0.40), to be genetically correlated with farrowing performance in PRRSV-infected sows, be controlled by two major QTL on chromosome 7, among others, and have moderate genomic prediction accuracy. However, waiting for PRRS outbreaks to occur to collect data limits the use of Ab response to select for increased PRRS resilience. Thus, we investigated the genomic basis of Ab response to PRRS vaccination with a modified live PRRSV vaccine as a strategy to generate data for this purpose. Nine hundred and six commercial F1 replacement gilts (189±16 days old) were vaccinated with a commercial PRRS modified live virus vaccine. Blood samples were collected 52 days after vaccination to measure Ab response, as sample-to-positive (S/P) ratio using a commercial ELISA, and for SNP genotyping (~50K). BayesC0 was used to estimate heritability for S/P ratio using in a model with contemporary group (CG) as fixed effect and SNP effects as random. Genome-wide association study and genomic prediction for S/P ratio were performed with BayesB (Pi=0.99). For genomic prediction, a three-fold cross-validation was used, in which each CG (n=3) was used as validation dataset. Accuracy of genomic prediction was defined as the correlation between genomic estimated breeding values and phenotypes adjusted for estimates of fixed effects, weighed by the number of individuals in the validation dataset. Heritability of S/P was moderate (0.35±0.04). A QTL was identified on chromosome 7 (25 Mb) explaining ~28% of the genetic variance. Accuracy of genomic prediction was fairly high (0.60±0.15). This is the first study describing the genomic basis of Ab response to PRRS vaccination with modified-live virus vaccine. Additional work is needed to evaluate the genetic correlation of Ab response to vaccination with resilience traits in pigs.